MEWUJUDKAN MASYARAKAT MADANI MELALUI OPTIMALISASI PELAYANAN PENDIDIKAN MASYARAKAT MARJINAL DENGAN PELATIHAN DIGITAL MARKETING - Rozaq, Muhammad Abdur; Jasran Asya; Hakim, Elsan Octavia; Fraistifina; Yunita Anggraeni; Kamelia; Prianto, Yuwono (Jurnal Serina Abdimas, 2024)
The idea to achieve civil society through education in reality faces the challenge of low School Enrollment Rates because of the poverty factors which have created marginalization of society. Furthermore, educational opportunities must be provided to prepare societies for the development of the digital age. Digital marketing training is a solution to provide students at Master School (Masjid Terminal) in Depok of West Java whose knowledge and expertise in the field of digital marketing is still limited to face current developments in the digital era by providing an explanation of the scope, potential and its application as well as providing practical experience that allows them to experience and understand the preparations needed so that they meet the human resources needs of the digital era, in order to realize a civil society by optimizing educational services. The training implementation method applied the ADDIE method, and included training needs analysis, design, development, implementation, and evaluation. The Training delivered using a combination of lecture, question and answer, and direct practice methods. It was executed in line with the designated design and development training and the participants gained new expertise and knowledge about digital marketing needed in the current era so that it will provide advantages for them.